Twin study on cup/disc ratio of the optic nerve head. - Teikari, J. M. (1992)
Seventeen healthy twin pairs (10 monozygotic and seven dizygotic) from the Finnish Twin Cohort Study were examined to study the impact of heredity v environment in the determination of cup-to-disc area ratio. These twins were free from any known eye disease. The cup/disc ratio was determined using stereo photography and a computer assisted analysis technique. The zygosity of all twin pairs was confirmed with the DNA 'fingerprint' technique. The intrapair correlations were high among monozygotic pairs compared with those among dizygotic twin pairs. The difference of cup/disc area ratios between the right eyes of members of monozygotic twin pairs was statistically significantly smaller than that of dizygotic twin pairs (p < 0.001). The same was true for left eyes (p < 0.01). This result confirms a genetic determination in cup/disc area ratio in normal eyes.